Medium term health and quality of life outcomes in a cohort of children with MIS-C in Cape Town, South Africa - Phoya, Frank (Department of Paediatrics and Child Health, 2026)
Background: Multisystem inflammatory syndrome in children (MIS-C) is a disease that occurs after exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Its short term effects have been documented but little data exist on the longer term effects of MIS-C on the health and quality of life of patients. The objective of this study was to assess the long-term effects of MIS-C on the quality of life of children. Methods: This study was a prospective, case control, cohort study. We included 24 participants with previous MIS-C and 20 children with juvenile idiopathic arthritis (JIA) as a positive comparator group. All children were examined and completed a paediatric quality of life (PedsQL) generic inventory score. This score was used to evaluate the school functioning, social, emotional, and physical domains of the two groups. Results: All participants with previous MIS-C made a full recovery with normal physical examination after a median of 705 days after acute MIS-C. The PedsQL inventory revealed that 16.7% of the children with previous MIS-C showed a deficit in the physical domain compared to 60% of the children with JIA (p<0.001). There was a deficit in the psychosocial domain (which combines emotional, social and educational scores) in 12.5% children with previous MIS-C compared to 40% children with JIA (p=0.035) Conclusions: In 24 children with previous MIS-C, after approximately 2 years, no medical complications were reported. A small proportion felt a prolonged effect on their quality of life even after making a full recovery, which was less severe than in children with JIA. This highlights the need to continue to follow up these patients and offer more comprehensive long-term care.